Estrogen regulation of placental angiogenesis and fetal ovarian development during primate pregnancy - Albrecht, Eugene D. (2010)
During human and nonhuman primate pregnancy, an extensive blood vessel network is established within the villous placenta to support fetal growth and follicles develop within the fetal ovary to provide a pool of oocytes for reproductive function in adulthood. These two important developmental events occur in association with a progressive increase in placental estrogen production and levels. This review will describe the developmental processes required for placental vascularization and fetal follicular maturation and recent studies which show that estrogen has an important role in regulating these events.